THE EFFECT OF AUDITOR QUALITY ON BOND RATING: THE TESTING OF "INFORMATION ROLE" AUDITORS IN INDONESIA - Sri Wahyuni (Journal of Economics, Business, and Accountancy Ventura, 2013)
Measuring the company bond rating is important for the business nowadays. Auditor qualityis considered an important factor. Therefore, it is important to see the effect of auditor qualityon bond rating. The objective of this research is to investigate the relation between auditorquality characteristics (size, tenure and industry specialist auditors), and bond rating.Data used in this research are 1283 years-firm observation during 2000-2010. The results ofthis research find that auditor quality characteristics, auditor size and industry specialistauditor has a positive significant affect to bond rating, but auditor tenure not significant. Thecontrolled variables as firm size, profitability, coverage, firm age, maturity, and bond sizeand bank debt are factored into firm’s bond rating by credit rating agencies. Overall, ourresult suggests that trough their role of providing information, auditor quality (size and specialistindustry) are important factors for the market participants.